Enhancing Linear Programming Education Through Comprehensive and Maritime Relevant Teaching Materials - Putri Nurul Hilda Syani; Fera Mirta; Siregar Nur Asma Riani (SHS Web of Conferences)
This research aims to identify the needs of students for teaching materials in the Linear Programming course at Raja Ali Haji Maritime University, emphasizing the completeness of the material and its relevance to maritime contexts. The findings indicate that most students struggle to find textbooks that cover all the necessary topics in Linear Programming. They reported that the existing learning resources do not adequately address all of the subjects being taught. Furthermore, the teaching materials currently in use have not been integrated with maritime contexts, despite their significance for students living in the maritime-based region of the Riau Islands. This research recommends developing teaching materials that are more comprehensive, easily accessible, and aligned with maritime contexts to enhance learning effectiveness and increase the material's relevance to students' everyday lives. Ultimately, creating teaching resources that incorporate the local context can support the vision of maritime-based education in the Riau Islands and strengthen students' competencies as they prepare to face challenges in a job market that increasingly demands skills connected to real-world applications.